BIOETIKA PENELITIAN BIOEKOLOGI MANGROVE DI PANTAI CEMARA LEMBAR, KABUPATEN LOMBOK BARAT - Fadiya Utami; Muhammad Zul Hilmi; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Cemara Beach in Lembar, West Lombok, is a coastal ecosystem dominated by mangrove vegetation that plays an important ecological role in coastal protection and biodiversity support. This study aims to analyze the bioecological characteristics of mangrove vegetation and integrate bioethical principles in research implementation. The method used is purposive sampling with a belt transect approach for ecological data collection and descriptive observation for bioethical aspects. The results show that mangrove density is relatively moderate, with dominant species such as Rhizophora sp. and Avicennia sp., but facing anthropogenic pressures from tourism and coastal activities. The application of bioethical principles, especially non-maleficence and respect for local communities, is essential to ensure sustainable research and conservation efforts.